The role of the national hydrological and meteorological services in managing crisis risk related to natural disasters on the example of the Institute of Meteorology and Water Management – National Research Institute - Derek, Paweł (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
Climate change causing extreme natural hazards is significantly reflected in material and human losses. The World Meteorological Organization (WMO), aware of the growing problem, recommends the role of national hydrological and meteorological services in national crisis management structures. The article analyzes the implementation of the requirements set by WMO in relation to the tasks of the Institute of Meteorology and Water Management – National Research Institute which is an active participant in processes in state crisis management structures. The tasks defined for IMGW-PIB by applicable regulations are in line with WMO expectations. It should be expected that they will evolve along with the intensification and frequency of diversity of natural phenomena.